The Effect of Fatimid Dynasty Authority Toward the Development of Islamic Education in Egypt - Daud, Al Husaini M (SCAD Independent, 2022)
This article discussed the influence of the Fatimid Dynasty authority on the development of Islamic education in Egypt. The objective of this article was only to discuss the penetration of the Fatimid authority in developing Islamic education during this empire in Egypt led in which started since al-Muiz Lidinillah until the last Fatimid Caliph in Egypt. It was qualitative research applying a historical approach. The author found that socially, Egyptian society consisted of a group of Sunni and Shi'a, Africans who became the Fatimid army, the Turks who had settled in Egypt, the Ahl Dhimmah composed of Jewish and Christian, and Sudanese people who lived in Egypt. While the government system of the Fatimid Dynasty was a theocracy with the source of law based on the principle of al-Quran and Hadith related by Reviews their priests. Meanwhile, the influence of authority of this empire wasshown on the effort of Caliphs in building some Islamic educational institutions, Reviews such as the palace, mosque, house of wisdom (Dar al-Hikmah), libraries, and universities. In addition, the Caliph did not hesitate to issue a financial state in large numbers for the development of knowledge by Bringing learning resources from abroad and also sponsored the translation of foreign literature into Arabic.